Talk in interaction: Comparative dimensions - Haakana, Markku; Laakso, Minna; Lindström, Jan (Studia Fennica Linguistica, 2009)
"During the recent decades Conversation Analysis has developed into a distinctive method for analyzing talk in interaction. The method is utilized in several disciplines sharing an interest in social interaction, like anthropology, linguistics, social psychology, and sociology, and it has been applied to a great variety of languages and types of interaction. Conversation Analysis then is coming of age as a truly comparative enterprise. This volume presents and discusses comparative approaches to analyzing interactional practices and structures. The contributors to the volume have their background in sociology, linguistics, and logopedics. They offer comparative analyses of activity types, participant roles and identities, displays of emotion, and design of actions such as questions and corrections. The languages covered by the chapters include English, Finnish, German, and Swedish. This volume is of interest to all those interested in the research of language and social interaction. Because of its methodological nature, the book can also be utilized in teaching and in learning the discovery procedures typical of Conversation Analysis. "